Rancang Bangun Pakan Ikan Otomatis dan Kontroling Suhu Serta Monitoring pH Air Berbasis IoT - Robiyanto, Robi; Subakti, Tresna; Raswa; Al Hilmi, Muhammad Anis (Fakultas Teknik Universitas Persada Indonesia YAI, 2025)
This research proposes the design of an automatic fish feeding system equipped withtemperature control and water pH monitoring based on the Internet of Things (IoT). Thissystem aims to increase efficiency in aquarium or fish pond management by integratingvarious control and monitoring functions in real-time. In this system, the automatic fishfeeder uses a programmable dispenser mechanism to provide feed in predeterminedamounts and times. Temperature control is carried out using temperature sensors andheating or cooling actuators, to maintain water temperature conditions within the optimalrange. In addition, water pH monitoring is carried out through a pH sensor connected tothe system to ensure the water quality remains ideal for fish health. Data from these sensorsis sent in real-time to the IoT platform, enabling remote monitoring and control via webbasedor mobile applications. The results of implementing this system show increasedefficiency in feeding, increasing operational efficiency, reducing human error, andproviding quality fish, as well as maintaining more stable and optimal environmentalconditions. The implementation of this system shows great potential in modern aquacultureapplications by utilizing IoT technology for better and responsive management.